Evaluación técnica de la inyección cíclica de agua en la formación K1 inferior del campo Castilla mediante simulación numérica (2019)
In this dissertation, a technical feasibility study for cyclic water injection in Castilla Field is presented managing numerical simulation through CMG software, a great variety of time responses were tested, in order to find the optimal cyclic injection and rise the oil recovery in two patterns located in the north central part of Castilla field. The best response in terms of an increase in oil production was given by the pattern I2 performing two-month closing and opening cycles due to that case generated an incremental oil of 3.16% compared to conventional waterflooding.